The effects of COVID-19 severity on health status in Kazakhstan: A prospective cohort study - Elmira Kaidar; Assiya Turgambayeva; Baurzhan Zhussupov; Rimantas Stukas; Timur Sultangaziyev; Beibut Yessenbayev (Elsevier, 2024)
On May 5, 2023, the World Health Organization announced the end of the coronavirus pandemic. Nonetheless, there are growing reports indicating that individuals who have contracted COVID-19, especially in its more severe manifestations, may endure medium-to long-term impacts of the condition.The purpose of this study was to investigate the impact of the severity of COVID-19 on the subsequent health outcomes. Methods: The prospective cohort study ran from March to October of 2021.482 study participants were divided into two cohorts: the first cohort encompassed 118 individuals who received hospital care, while the second cohort included 364 individuals receiving outpatient care. Propensity Score Analysis was used as the probability of being hospitalized for COVID-19 in logistic regression as a covariate, to account for the influence of intervening factors that were associated with the probability of being hospitalized for COVID-19. The odds ratio (OR) was the association metric that was applied. Results: Patients with more severe COVID-19 are more prone to infectious and parasitic diseases ORadj 6.61 (with 95 % CI 1.84-23.75), p = 0.004, more likely to show complications from the respiratory system ORadj 2.37 (with 95 % CI 1.35-4.16), p = 0.003, more frequently diagnosed eye pathologies ORadj 5.60 (with 95 % CI 1.96-15.98), p = 0.001, susceptible to hospitalization, ORadj 3.49 (1.78-6.84), p < 0.001. Conclusion: Our study's findings indicate that patient with more severe COVID-19 have a higher requirement for medical attention regardless of other factors that influence the need for medical care.